QUALITATIVE EVALUATION OF ENDOPARASITES OF FELINES SEMI DOMICILED IN THE MUNICIPALITY OF MARINGÁ, PARANÁ, BRAZIL - Beatriz Pereira, Bruna (2019)
The occurrence of endoparasitoses in domestic animals has been reported routinely in the medical clinic of small animals, where wandering and domiciled cats are considered important reservoirs, evidencing the role of felines in the contamination of the environment by the infective forms of these parasites. Many animals are asymptomatic, but those with high parasitic load evidence clinical signs such as inappetence, anorexia, vomiting and diarrhea. The present study aimed to identify the different parasites found in faecal samples of semi - domed felines; for this, 45 fecal samples of cats were collected, regardless of age, sex or race, from different households in the municipality of Maringá, PR, Brazil. The collected samples were submitted to coproparasitological tests by means of the Willis & Mollay flotation method, carried out in the Veterinary Parasitology laboratory of the Veterinary Clinic of Uningá, Centro Universitário Ingá (UNINGÁ) between April and May 2017 The results obtained confirmed infestation by Toxoplasma gondii (Nicolle & Manceaux, 1908), Cryptosporidium sp. (Tyzzer, 1907), Cystoisospora sp. (Frenkel,1977), Giardia sp. (Kunstler,1882), Strongyloides sp. (Bavay, 1876), Toxocara cati (Schrank, 1788), Ancylostoma tubaeforme (Zeder, 1800), Toxascaris leonina (Sprent,1959) and Dipylidium sp. (Leuckart, 1886). Therefore, the study emphasizes the periodic monitoring of coproparasitological examsin the clinical routine of small animal clinics in order to minimize enteric alterations and pharmacological resistance.